Acute and Persistent Postoperative Functional Decline in Children with Severe Neurological Impairment: A Qualitative, Exploratory Study - Liisa Holsti; Sarah England; Mackenzie Gibson; Bethany McWilliams; Anne-Mette Hermansen; Harold Siden (MDPI AG, 2024)
Background: Children with severe neurologic impairment (SNI) regularly require major surgery to manage their underlying conditions. Anecdotal evidence suggests that children with SNI experience unexpected and persistent postoperative functional changes long after the postoperative recovery period; however, evidence from the perspective of caregivers is limited. The purpose of the study was to explore the functional postoperative recovery process for children with SNI. Methods: Eligible participants were English-speaking caregivers of children with SNI between 6 months and 17 years who were nonverbal, Gross Motor Function Classification Scale level IV/V, and who had surgery/procedure requiring general anesthetic at a tertiary children's hospital between 2012 and 2022. Demographic and basic health information were collected via surveys and corroborated by a review of the child's electronic health record. Semi-structured interviews were conducted and a thematic content analysis was used to formulate results. Results: Data from 12 primary caregiver interviews revealed four main themes: (1) functional changes and complications in the child; (2) feeling unprepared; (3) perioperative support; and (4) changes to caregiver roles. Conclusions: Postoperative functional decline in children with SNI was prevalent in our sample. Providing pre-operative information to families to describe this phenomenon should be a regular part of family-informed care.